2005
DOI: 10.1158/0008-5472.can-04-1833
|View full text |Cite
|
Sign up to set email alerts
|

A 27-Amino-Acid Synthetic Peptide Corresponding to the NH2-Terminal Zinc-Binding Domain of Endostatin Is Responsible for Its Antitumor Activity

Abstract: The first recombinant endostatin that elicited strong antitumor activity was expressed in Escherichia coli and administered as a suspension. Under these conditions, the protein retained its full antiangiogenic activity. Lack of requirement for a folded structure prompted us to investigate antitumor properties of synthetic peptides corresponding to different regions of endostatin. Here, we show that the entire antitumor, antimigration, and antipermeability activities of endostatin are mimicked by a 27-amino-aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 35 publications
2
85
1
1
Order By: Relevance
“…However, this peptide was treated at the tumor periphery and for only 7 days. In another study (49), a minimum sequence of 27 amino acid synthetic peptide corresponding to the N-terminal zinc-binding domain of endostatin fully mimicked its antitumor activity. However, the peptide was administrated at a higher frequency (twice a day vs. once a day for fulllength endostatin).…”
Section: Minimum Endostatin Sequence Required For Its Biological Actimentioning
confidence: 96%
“…However, this peptide was treated at the tumor periphery and for only 7 days. In another study (49), a minimum sequence of 27 amino acid synthetic peptide corresponding to the N-terminal zinc-binding domain of endostatin fully mimicked its antitumor activity. However, the peptide was administrated at a higher frequency (twice a day vs. once a day for fulllength endostatin).…”
Section: Minimum Endostatin Sequence Required For Its Biological Actimentioning
confidence: 96%
“…However, the antiangiogenic activity has been shown to reside in different regions of the molecule by different groups. For instance, a peptide encompassing the secondary heparin-binding site was the minimal active domain in one in vivo study (Olsson et al, 2004) and the N-terminal 29 amino acids critical in another (Tjin Tham Sjin et al, 2005). While both peptides are antiangiogenic, it is not clear whether they function by the same intracellular effector pathways as each other or as parental endostatin.…”
Section: Peptide Fragmentsmentioning
confidence: 99%
“…20 Recently, we have shown that an NH 2 -terminal 27-aminoacid synthetic peptide of endostatin, corresponding to the zinc-binding domain, is responsible for its antitumor properties. 21 Gene therapy is a feasible approach to combat cancer, with a sustained systemic therapeutic release of antiangiogenic substances and a highly localized delivery. Sustained elevated blood levels obtained by continuous administration from an implanted pump have been demonstrated to be significantly more effective against tumors in animals than intermittent peak levels from bolus dosing.…”
Section: Introductionmentioning
confidence: 99%